Respon Pertumbuhan Pakcoy (Brassica chinensis L.) terhadap Pemberian POC Limbah Baglog Jamur dan Kulit Semangka - Yassar Rahma Istikomah; Suparti Suparti (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Pakcoy (Brassica chinensis L.) is a vegetable from the Brassicaceae family. Pakcoy is a short-lived plant. Pakcoy contains fat, protein, Fe, Ca, P, Vitamins A, B, C, E, and K, with that pakcoy is very good for health and has prospects for high economic value. The first factor affecting the decline in pakcoy production is soil fertility. The continuous use of land with chemical fertilizers results in a decrease in biological, chemical and physical soil fertility, one of the efforts to overcome this problem is to improve cultivation techniques through fertilization. This study aims to determine the growth response of the pakcoy plant by administering liquid organic fertilizer from mushroom baglog waste and watermelon rinds. This study used a factorial complete randomized design with 2 factors, namely the interval of watering of liquid organic fertilizer and the volume of organic fertilizer dilution concentration and used quantitative descriptive analysis with the Two Way ANOVA test. The purpose of this study was to determine the growth response of the pakcoy plant to the application of liquid organic fertilizer from mushroom baglog waste and watermelon rinds. The results of this study indicated that the TIV3 treatment (watering interval once every 3 days with a volume of 30% dilution concentration) gave a response to plant height with an average of 18.05 cm, number of leaves with an average of 6 leaves, and an average fresh weight of 11.50 g.